Purified Vitexin Compound 1 Inhibits UVA-Induced Cellular Senescence in Human Dermal Fibroblasts by Binding Mitogen-Activated Protein Kinase 1 - Wang, Ben; Yan, Sha; Yi, Yuxin; Huang, Yingxue; Deng, Zhili; Zhang, Yiya; Zheng, Qingchuan; Xie, Hongfu; Li, Ji (Frontiers in Cell and Developmental Biology, 2020)
Purified vitexin compound 1 (VB1), a novel lignanoid isolated from the seeds of the Chinese herb Vitex negundo, has strong antioxidant abilities and broad antitumor activities. However, little is known about its anti-photoaging effect on the skin and the underlying mechanism. Here, we demonstrated that VB1 significantly attenuates ultraviolet A (UVA)-induced senescence in human dermal fibroblasts (HDFs), as evidenced by senescence-associated β-gal staining, MTT assays, and western blot analysis of the expression of p16 and matrix metalloproteinase-1 (MMP-1). Furthermore, mass spectrometry revealed that VB1 could directly bind to Mitogen-Activated Protein Kinase 1 (MAPK1). Molecular docking and molecular dynamics simulation methods confirmed the mass spectroscopy results and predicted six possible binding amino acids of MAPK1 that most likely interacted with VB1. Subsequent immunoprecipitation analysis, including different MAPK1 mutants, revealed that VB1 directly interacted with the residues, glutamic acid 58 (E58) and arginine 65 (R65) of MAPK1, leading to the partial reversal of UVA-induced senescence in HEK293T cells. Finally, we demonstrated that the topical application of VB1 to the skin of mice significantly reduced photoaging phenotypes in vivo. Collectively, these data demonstrated that VB1 reduces UVA-induced senescence by targeting MAPK1 and alleviates skin photoaging in mice, suggesting that VB1 may be applicable for the prevention and treatment of skin photoaging.